MODEL PEMBELAJARAN BERBASIS TEORI MULTIPLE INTELLIGENCES: PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN MATEMATIKA - Rizqona Maharani (INSPIRAMATIKA, 2015)
The theory of multiple intelligences developed by Howard Gardner who pointed to the existence of various types of intelligence possessed by each individual. This theory is widely used in education, namely as a reference in designing learning activities that can include the diversity of the student's natural ability (intelligence). Gardner proposes nine types of intelligence, namely logical-mathematical, linguistic, interpersonal, intrapersonal, musical, visual-spatial, bodily kinesthetic, existentialist, and naturalist intelligence. Based on the theory of multiple intelligences, educators can choose a model of teaching mathematics that able to accommodate students’ learning needs as well as develop, and optimize the intelligences of the students. One of the model that can be applied is a cooperative learning modified with scientific approach. Some cooperative learning models with scientific approach can be used in teaching mathematics are TSI with scientific approach (TSI-PS), TPS with scientific approach (TPS-PS), TGT with scientific approach (TGT-PS), GI with scientific approach (GI-PS). These models provide a lot of options on mathematics learning activities which are line with characteristics of students’ intelligences.